Impact of primary cancer features on behaviour of colorectal liver metastases and survival after hepatectomy. Issue 2 (3rd September 2018) - Cucchetti, A; Russolillo, N; Johnson, P; Tarchi, P; Ferrero, A; Cucchi, M; Serenari, M; Ravaioli, M; de Manzini, N; Cescon, M; Ercolani, G
Abstract: Background: Markers of tumour biology may be valuable prognostic indicators after hepatic resection of colorectal cancer liver metastases (CRLMs). Identification of the aggressiveness of these metastases might inform the appropriateness of hepatic surgery. Methods: Patients undergoing liver resection for CRLMs between January 2001 and July 2013 in four tertiary hospitals were reviewed. A mathematical model to estimate CRLM doubling times was constructed for patients with metachronous metastases. Tumour doubling time was investigated in relation to the features of colorectal cancer, including KRAS status. The hazard rate for recurrence and death following hepatectomy was explored through the Kernel-smoothed estimator. Results: Of 1063 patients undergoing liver resection for CRLMs, 361 with metachronous metastases undergoing single-stage hepatectomy were analysed. The mean doubling time in patients not receiving chemotherapy between surgery for colorectal cancer and CRLM was 71·4 days. Tumour doubling time was shorter in patients with more advanced primary tumour stages, with mutant KRAS and in those who did not receive chemotherapy. For fast-growing CRLMs (doubling time less than 48 days), the risk of recurrence was highest within the first postoperative year, and was about 7 per cent per month. Conclusion: Primary features of colorectal cancer were linked to aggressiveness of CRLMs as measured by doubling time. Graphical Abstract: Data from 361 patients who underwent resection for metachronous colorectal liver metastases (CRLM) were used to estimate tumor doubling times for use as an indicator of tumor aggressiveness. The mean doubling time was 71·4 days in patients not receiving chemotherapy and was shorter in those with more advanced primary tumor stage and mutant KRAS . For fast-growing CRLMs, the risk of recurrence was up to 7% within the first postoperative year, whereas for slow-growing CRLMs this risk did not exceed 3·3%. More work needed on doubling times